2013
DOI: 10.1590/s1984-29612013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of parasitic cysts in the brains of a flock of sheep in Egypt

Abstract: Cerebral parasitic cysts constitute a major problem for livestock. Among these, coenurosis and toxoplasmosis are predominant. Here, a total number of 60 sheep obtained from a private farm in Suez province, Egypt, were examined postmortem to detect visible parasitic cysts, and microscopically to detect small-sized entities. Necropsy revealed bladder-like cysts measuring 0.5-6.5 cm in diameter that were filled with a translucent fluid containing a large number of protoscolices. Accordingly, the cysts were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…In the present study, prevalence rate of C. cerebralis cysts in Madras red sheep was 12.30 % (Table 1). Similar findings were observed by Gicik et al (2007), Tavassoli et al (2011) and Anwar et al (2013), who found that 15.50, 18.65 and 18.30 % of sheep were infected with C. cerebralis cysts in Turkey, Iran and Egypt, respectively. Other authors reported the prevalence of Coenurus cysts in brain ranging from 0.35 to 9.8 % in sheep (Panisup et al 1979;Karim 1979;Akkaya and Vurusaner 1998;Varma and Malviya 1989;Oryan et al 1994;Bussell et al 1997;Achenef et al 1999;Abo-Shehada et al 2002;Scala et al 2007).…”
Section: Resultssupporting
confidence: 88%
“…In the present study, prevalence rate of C. cerebralis cysts in Madras red sheep was 12.30 % (Table 1). Similar findings were observed by Gicik et al (2007), Tavassoli et al (2011) and Anwar et al (2013), who found that 15.50, 18.65 and 18.30 % of sheep were infected with C. cerebralis cysts in Turkey, Iran and Egypt, respectively. Other authors reported the prevalence of Coenurus cysts in brain ranging from 0.35 to 9.8 % in sheep (Panisup et al 1979;Karim 1979;Akkaya and Vurusaner 1998;Varma and Malviya 1989;Oryan et al 1994;Bussell et al 1997;Achenef et al 1999;Abo-Shehada et al 2002;Scala et al 2007).…”
Section: Resultssupporting
confidence: 88%
“…Some animals may present a serious infection when the larvae enter the brain through the foramina and they may develop encephalitis, manifesting ataxia, hemiparesis and blindness (Mozaffari et al 2013). Severe injury of the brain tissue may produce a characteristic behavior in sheep known as "gid" which resembles the lesion produced by Coenurus cerebralis, the larval stage of Taenia multiceps (Anwar et al 2013). Considering the cold winter season in southern Chile, the presence of new infections can only be observed from late spring to early autumn, coinciding with the reproductive activity of adult flies.…”
Section: Introductionmentioning
confidence: 99%
“…Although, neurological signs caused by C. cerebralis are common among sheep and goats, some animals remain normal and seemed to be healthy, and were diagnosed only after death (Sharma and Chauhan, 2006). Previously in Egypt, C. cerebralis infection was estimated as 18.3% in a sheep flock from Suez Canal province (Anwar et al, 2013). Desouky et al (2011) reported 100% prevalence in clinically diseased sheep from Cairo, although they did not found any cysts in the apparently healthy animals.…”
Section: Discussionmentioning
confidence: 95%